DEVELOPMENT OF INTERACTIVE MULTIMEDIA BASED ON ISPRING SUITE 9 IN THEMATIC LEARNING IN BASIC EDUCATION - Reynara Munawara Isaura; Robiatul Munajah (Universitas Islam Negeri Mataram, 2024)
This research aims to develop interactive multimedia learning media based on iSpring Suite 9 in thematic learning in class III at SDN Kalideres 12 Pagi. This research uses the Borg and Gall development model. Research subjects in class III of SDN Kalideres 12 Pagi with 32 students. The objectives in developing this media include: 1) to produce interactive multimedia learning media based on Ispring Suite 9 in class III thematic learning, 2) to determine the level of feasibility of interactive multimedia learning in class III thematic learning, and 3) to determine the effectiveness of interactive multimedia learning on the learning outcomes of class III. The results of this research are products in the form of interactive multimedia based on iSpring Suite 9 with validation results from media design experts of 90.27%, material experts of 96.25% in the